Exploitation as Theft vs. Exploitation as Underpayment - Rodgers, Lamont (2015)
Marxists claim capitalists unjustly exploit workers, and this exploitation is to show that workers ought to hold more than they do. This paper presents two accounts of exploitation. The Theft Account claims that capitalists steal some of the value to which workers are entitled. The Underpayment Account holds that capitalists are not entitled to pay workers as little as they do, even if the workers are not entitled to the full value they produce. This paper argues that only the Theft Account can explain why workers ought to hold more than they do. The Underpayment Account cannot yield this conclusion. The Theft Account is superior to the Underpayment Account insofar as exploitation is to be an injustice—a wrong that requires the exploited party to hold more.